Manajemen Bahan Baku dan Produktivitas Produksi Pempek Ikan Tenggiri pada Usaha Evi Tenggiri Pulau Baai Kota Bengkulu - Indra Lesmana Saputra; Herri Fariadi; Ana Nurmalia (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2026)
Evi Tenggiri business in Pulau Baai, Bengkulu City is a Spanish mackerel fish pempek processing business that faces challenges in raw material management, especially related to fluctuations in fish availability and quality and the efficiency of production input use. This study aims to analyze raw material management and production productivity at Evi Tenggiri Business. The research was carried out in January 2026 at TPI Pulau Baai, Sumber Jaya Village, Bengkulu City, using quantitative methods and a descriptive approach through observation, interviews, and the distribution of questionnaires to the business owner. The results of the study show that raw material management has been carried out systematically through stages of needs planning, procurement from fishermen and local traders, storage using freezers at temperatures ≤ –18°C for fish and dry rooms for tapioca flour, and routine quality control. Productivity analysis shows that the productivity of minced fish raw material is 3.65 kg pempek/kg fish (high category), tapioca flour productivity is 2.20/kg pempek/kg tapioca (medium category), and labor productivity is 858.33 kg/employee/month or 33.01 kg/employee/day. Overall, structured raw material management contributes positively to increased production productivity at Evi Tenggiri Business.